If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 = -7.5z + -1(-7z + 3) Reorder the terms: -7 = -7.5z + -1(3 + -7z) -7 = -7.5z + (3 * -1 + -7z * -1) -7 = -7.5z + (-3 + 7z) Reorder the terms: -7 = -3 + -7.5z + 7z Combine like terms: -7.5z + 7z = -0.5z -7 = -3 + -0.5z Solving -7 = -3 + -0.5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '0.5z' to each side of the equation. -7 + 0.5z = -3 + -0.5z + 0.5z Combine like terms: -0.5z + 0.5z = 0.0 -7 + 0.5z = -3 + 0.0 -7 + 0.5z = -3 Add '7' to each side of the equation. -7 + 7 + 0.5z = -3 + 7 Combine like terms: -7 + 7 = 0 0 + 0.5z = -3 + 7 0.5z = -3 + 7 Combine like terms: -3 + 7 = 4 0.5z = 4 Divide each side by '0.5'. z = 8 Simplifying z = 8
| log[4](2x-9)-log[4](x-8)=3 | | 3(x+9)=6x | | 2=x-4(2x+3) | | 8(r+2)=54 | | 7x=12x-45 | | (+15)+(-7)+(+1)= | | y=57-2 | | 2x+4x=3x+3 | | 3(x-9)=6x | | 1/5y=9-2/5y | | 4c-6=-2 | | 2n+5+4=-1 | | 4C-6=two | | xb=ya | | 2x=11+x | | 6x+1=6(x+1) | | Y=0.15x+0.55 | | 5(15+x)=-70 | | 2*5+8/2=18 | | 2.49+x= | | 9x+1/3x=0 | | 0.20(y-4)+0.16y=0.02y-0.07(60) | | 9x+3x=0 | | (4b+3b^4)-(2b-8b^4)+(5b+9b^2+6b^4)= | | 0.2m=0.3m+2.4 | | 16x^2+32x-65=0 | | m+33=112 | | -12+12=y | | 20-12=2x | | X+5x/3=24 | | 2/3(x-5)=-10+4 | | 3(m-4)+5=5m-21 |